1999
DOI: 10.1016/s0927-7757(98)00868-1
|View full text |Cite
|
Sign up to set email alerts
|

Dewatering characteristics of algae-containing alum sludge

Abstract: The presence of algae in source waters not only causes problems in the water treatment process, but also complicates the treatment and disposal of sludge. This has become a major concern in Taiwan because of the increasing eutrophication of water sources. The purpose of this study was to determine the effects of algae during aging process on the characteristics of potable water treatment residuals and investigate their conditioning in order to provide water treatment plants with guidelines for treating algae-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 10 publications
(16 reference statements)
0
16
0
Order By: Relevance
“…Over the course of the sludge storage, the pH and the total solids content remained unchanged (Pan et al, 1999). The TOC, zeta potential, and bound water content, however, decreased throughout storage (Pan et al, 1999).…”
Section: Section 252 Settling Characteristics Of Activated Sludgementioning
confidence: 98%
See 4 more Smart Citations
“…Over the course of the sludge storage, the pH and the total solids content remained unchanged (Pan et al, 1999). The TOC, zeta potential, and bound water content, however, decreased throughout storage (Pan et al, 1999).…”
Section: Section 252 Settling Characteristics Of Activated Sludgementioning
confidence: 98%
“…However, enhanced bioflocculation was achieved during stationary growth phase given greater amounts of EPS were present over the uronic acids present (uronic acids with respect to EPS was low) (Badireddy et al, 2010). Therefore, In a study by Pan et al (1999), algal biomass was shown to improve the dewatering characteristics and bioflocculation capability of activated sludge. In this study, sludge with Pediastrum, Ankistrodesmus, and some diatom algal species was aged in a container free of sunlight.…”
Section: Section 252 Settling Characteristics Of Activated Sludgementioning
confidence: 99%
See 3 more Smart Citations